conseling PROGRAM PELATIHAN PEER COUNSELING SEBAGAI UPAYA LAYANAN PREVENTIF DI SEKOLAH - muhammad, fuadi; Muhammad Iqbal Dewantara (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2021)
Students' understanding of the importance of the need for counseling services in schools should always be campaigned by school counselors, but the obstacles that occur in the field are very much an obstacle for counselors. The presence of peer counseling training is expected to be an alternative solution that is preventive in nature and students are more open when sharing or venting with their peers. Peer counselors are expected to become facilitators to explore problems or diagnose peer problems before they get treatment from professionals. The results of this study proved that the enthusiasm of prospective peer counselors in following and simulating peer counseling activities was very good and maximal.